2021
DOI: 10.2147/ccid.s333221
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acne with Face Mask in Healthcare Workers Amidst the COVID-19 Outbreak in Karachi, Pakistan

Abstract: Background: In the wake of coronavirus (COVID-19) global alert, people have begun to practice safety measures in order to reduce the exposure to life-threatening disease. The largest at risk population is undoubtedly the frontline healthcare workers (HCWs) who are using personal protective equipment (PPE), essentially face masks, to battle against this deadly virus. This study was conducted with the prime intention to reveal an association between face mask and acne and measure the prevalence of acne amongst H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
1
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 23 publications
7
38
1
3
Order By: Relevance
“…Our study also revealed that females were 3.4 times more likely to suffer from mask-induced dermatological problems. More than half of females in our study reported dermatological problems similar to another study (53.4%) done in Pakistan [ 9 ]. Besides, wearing a face mask can accentuate dermatological problems (i.e., autoimmune diseases, allergic diseases, pigment disorders, and hair diseases), which are generally more common in females [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study also revealed that females were 3.4 times more likely to suffer from mask-induced dermatological problems. More than half of females in our study reported dermatological problems similar to another study (53.4%) done in Pakistan [ 9 ]. Besides, wearing a face mask can accentuate dermatological problems (i.e., autoimmune diseases, allergic diseases, pigment disorders, and hair diseases), which are generally more common in females [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…According to epidemiologic data, droplets produced during face-to-face encounters when talking, coughing, or sneezing appear to be the most common transmission mechanism [ 8 ]. Since health care workers (HCWs) come in direct contact with COVID-19 patients, they are prone to danger from this highly infectious virus [ 9 ]. When caring for COVID-19 patients, using personal protective equipment (PPE) may significantly lower the risk of infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a Turkish survey, conducted from December 2020 to February 2021, 101 healthcare workers (HCW) were screened for facial dermatoses and it emerged that acne prevalence was present in 55.4% of participants [4]. Similar findings resulted from another survey among HCW from Pakistan [5]. Acneiform eruptions have been documented in two larger cohorts of 454 [6] and 400 [7] subjects, where prevalence was respectively assessed to 39.9% and 43% of all adverse skin reactions due to prolonged face mask use.…”
Section: Introductionmentioning
confidence: 65%
“…In this study, we observed that about a quarter of the population reported new onset acne or worsening of preexisting acne. The 24.5% of the population sampled reporting acne is lower than that reported in studies in Singapore and Pakistan although these studies focused on healthcare workers who are thus more likely to wear face masks more consistently and for longer periods of time [ 20 , 21 ]. These numbers are high enough to be of concern especially as wearing of face masks is a key aspect of global NPI to reduce the spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%